Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
The required solution in terms of k is (k, (k-2)/2)
From the diagram, we are given the simultaneous equation expressed as:
-4y = -2x + 8 ................ 1
3x - 6y = 6
x - 2y = 2 ......................... 2
From equation 2, x = 2 + 2y ............... 3
Substitute equation 3 into 1 to have:
-4y = -2(2+2y) + 8
-4y = -4 -4y + 8
-4y + 4y = -4 + 8
0y = 4
y = 4/0
y = ∞
This shows that the systems of equations have infinite number of solution.
Let x = k
x = 2 + 2y
k = 2 + 2y
2y = k - 2
y = (k-2)/2
Hence the required solution in terms of k is (k, (k-2)/2)
Learn more on simultaneous equation here: https://brainly.com/question/386828
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.